Unbundling generators' reactive power output in a competitive market by using graph and circuit theory - Mustafa, Mohd. Wazir; Shareef, Hussain (Faculty of Electrical Engineering, Universiti Teknologi Malaysia, 2007)

(untitled)
This paper suggests a new method to allocate reactive power output of individual reactive power sources to system loads by tracing the current flow. Based on solved load flow and the network parameters, the method converts power injections and line flows into real and imaginary current injections and flows. These currents are then represented independently as real and imaginary current networks. Since current networks are acyclic lossless networks, proportional sharing principle and graph theory is used to trace the relationship between current sources and current sinks. The contributions from each current source are finally translated into reactive power contributions. The IEEE 14-bus system is used to illustrate the effectiveness of the method. Comparison of the results with previous methods is also given.